2019
DOI: 10.3390/polym11020269
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Way to Prepare Hydrophilic Homogeneous PES Hollow Fiber Membrane via Non-Solvent Assisted Reverse Thermally Induced Phase Separation (RTIPS) Method

Abstract: Sulfonated polyethersulfone (SPES) was used as an additive to prepare hydrophilic poly(ethersulfone) (PES) hollow fiber membranes via non-solvent assisted reverse thermally induced phase separation (RTIPS) process. The PES/SPES/N,N-dimethylacetamide (DMAc)/ polyethylene glycol 200 (PEG200) casting solutions are lower critical solution temperature (LCST) membrane forming systems. The LCST and phase separation rate increased with the increase of SPES concentrations, while the casting solutions showed shear thinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Figure 3 presents the results of the mean contact angle values obtained for each membrane. The values of the contact angle measured for the control membranes, 78.4 • for the PES membrane and 92.3 • for the PVDF membrane, are in agreement with the ones found for hollow fiber membranes in the literature [22][23][24][25].…”
Section: Hydrophilicitysupporting
confidence: 89%
“…Figure 3 presents the results of the mean contact angle values obtained for each membrane. The values of the contact angle measured for the control membranes, 78.4 • for the PES membrane and 92.3 • for the PVDF membrane, are in agreement with the ones found for hollow fiber membranes in the literature [22][23][24][25].…”
Section: Hydrophilicitysupporting
confidence: 89%
“…First of all, the dominant peaks were associated with strong C, O, and N signals in synthetic fibers, as well as with complex Cu and Se X-ray lines (Figure 11). Other investigators [29][30][31] also reported peaks corresponding to C, O, and N obtained from the analysis of untreated PAN fibers, PA6 fibers [32], PA66 [33], and PES fibers [34]. The Cu and Se peaks emanating from the Cu x Se coatings confirmed the formation of a welldefined thin coating layer.…”
Section: Sem and Edx Analysismentioning
confidence: 81%
“…Other investigators [29][30][31] also reported peaks corresponding to C, O, and N obtained from the analysis of untreated PAN fibers, PA6 fibers [32], PA66 [33], and PES fibers [34]. The Cu and Se peaks emanating from the CuxSe coatings confirmed the formation of a well-defined thin coating layer.…”
Section: Sem and Edx Analysismentioning
confidence: 82%
“…However, the formulation development and manufacturing phases of film dosage forms face numerous challenges that must be addressed to optimize the overall formulation, even during large-scale production [22]. As new technologies are rapidly introduced to prepare thin films, the future of film technology in the field of pharmaceuticals appears very promising [23].…”
Section: Introductionmentioning
confidence: 99%